Invisible invaders: unveiling the carcinogenic threat of microplastics and nanoplastics in colorectal cancer-a systematic review - Wen, Junkai; Lin, Yuhua (Frontiers in Public Health, 2025)
ObjectiveMicroplastics (MPs, 0.1–5000 μm) and nanoplastics (NPs, 0.001–0.1 μm) are ubiquitous environmental pollutants with strong persistence and bioaccumulation, posing significant threats to human health. Given their ability to penetrate biological barriers, accumulate in the food chain, and infiltrate human gastrointestinal tissues, humans ingest and inhale over 70,000 microplastic particles annually, and the observed higher abundance of MPs/NPs in colorectal tumor tissues in epidemiological data, this systematic review aims to explore the link between MPs/NPs exposure and colorectal cancer (CRC) carcinogenesis.MethodsThis study synthesizes 20 years of relevant research to systematically analyze the association between MPs/NPs exposure and CRC development.ResultsKey findings reveal that MPs/NPs enter the body via ingestion, inhalation, and dermal contact, translocating across biological barriers to induce DNA damage and oxidative stress through reactive oxygen species overproduction. They disrupt intestinal barrier function by reducing tight junction proteins, trigger chronic inflammation via pro-inflammatory cytokines, and cause gut microbiota dysbiosis. Additionally, MPs/NPs act as “Trojan horses”, adsorbing toxicants (e.g., bisphenol A) and pathogens, which exacerbate cytotoxicity and activate carcinogenic pathways.ConclusionThis review highlights the potential carcinogenic risk of MPs/NPs in CRC, deepens understanding of their mechanistic roles in carcinogenesis, and provides insights for the scientific management of MPs/NPs pollution.